PENGARUH KOMUNIKASI INSTRUKSIONAL BERBASIS BCCT (BEYOND CENTRE CIRCLE TIME) TERHADAP PEMBENTUKAN KARAKTER SISWA-SISWI PG-TK SEKOLAH ALAM BOSOWA KOTA MAKASSAR - Farannisa Ramil Putri; Jeanny Maria Fatimah; Arianto Arianto (Metacommunication: Journal of Communication Studies, 2023)
This study aims to determine BCCT-based instructional communication (Beyond Center and Circle Time) on the character building of PGTK students of Bosowa Natural School in Makassar City, where BCCT is the teaching and learning process of teachers and students form a circle so that the teacher's position is in line with the child's view. The focus of the study in this study is instructional communication which can be seen from five assessment indicators, ranging from the specification of instructional content and objectives, initial behavioral assessment, strategy determination, instructional unit organization, and feedback. The character-building assessment is based on the vision of PGTK Sekolah Alam Bosowa, namely Smart, Islamic, Discipline, Innovative and Competitive. To answer this question, a quantitative approach is used with a population and a sample of 30 students using a non-probability sampling technique or a saturated sample technique as a draw for the population below 30. The data analysis uses simple regression analysis, determination test and ANOVA test as a benchmark for the level of influence on several independent sub-variables. The results of this study were obtained as follows: 1) there is a positive and significant influence of BCCT-based instructional communication on smart character building in students with the highest level of relationship, 2) there is no influence of BCCT-based instructional communication on Islamic character building in students, 3) there is a positive and significant influence of BCCT-based instructional communication on discipline character building in students but the relationship very low. 4) there is a positive and significant influence of BCCT-based instructional communication on innovative character building in students, 5) there is a positive and significant influence of BCCT-based instructional communication on the formation of competitive character in students.